A robust brain network for sustained attention from adolescence to adulthood that predicts later substance use - Weng, Yihe; Kruschwitz, Johann; Rueda-Delgado, Laura M; Ruddy, Kathy L; Boyle, Rory; Franzen, Luisa; Serin, Emin; Nweze, Tochukwu; Hanson, Jamie; Smyth, Alannah; Farnan, Tom; Banaschewski, Tobias; et al. (eLife, 2024)
Substance use, including cigarettes and cannabis, is associated with poorer sustained attention in late adolescence and early adulthood. Previous studies were predominantly cross-sectional or under-powered and could not indicate if impairment in sustained attention was a predictor of substance use or a marker of the inclination to engage in such behavior. This study explored the relationship between sustained attention and substance use across a longitudinal span from ages 14 to 23 in over 1000 participants. Behaviors and brain connectivity associated with diminished sustained attention at age 14 predicted subsequent increases in cannabis and cigarette smoking, establishing sustained attention as a robust biomarker for vulnerability to substance use. Individual differences in network strength relevant to sustained attention were preserved across developmental stages and sustained attention networks generalized to participants in an external dataset. In summary, brain networks of sustained attention are robust, consistent, and able to predict aspects of later substance use.
Gesehen am 12.05.2025